Clinical and epidemiologic characterization of community acquired pneumonia. hospital "dr Israel Ranuarez Balza" Guárico. 2009-2010. (Revista Venezolana de Salud Pública, 2018)
The community-acquired pneumonia are those infections developed lung parenchyma within the general population. In the World is one of the most frequent causes of medical care, a current estimated incidence in the adult population of 2-10 year 1,000 population cases. That is why this research, which aims to characterize clinically and epidemiologically to community-acquired pneumonia arises. "Dr. Israel Ranuarez Balza "State Guárico. 2009-2010. An observational, descriptive, cross-sectional study where 138 stories, of which he took only included in the study 77 was used in the investigation, which had discharge diagnosis of pneumonia acquired in the community who had the inclusion criteria . The data were processed using the statistical package SPSS version 13.0. Obtained as important findings that is more common community-acquired pneumonia in males (63.64%) and in the age group of 25-44 years (40.26%), the most relevant findings are respiratory rate ≥ 20 rpm (78%), leukocytes ≥ 11,000 mm3 (60%), creatinine ≥ 1,2mgs / dl (44%), the most common radiologic localization are infiltrates in the lower lobes (48%) and multiple foci (26%)
Keywords: Pneumonia; Community; Lung disease